A review of microfluidic impedance sensors for pathogen detection - Chen Li; Mu Yuan; Zhian Li (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
The development of rapid, sensitive and specific methods for the detection of foodborne pathogens is important to ensure food safety. Currently, detection methods such as counting methods, immunoassays, and biosensors have been developed for detecting foodborne pathogenic bacteria, and impedance sensors combined with microfluidic technology have received extensive attention. This paper outlines the advances and applications of microfluidic impedance biosensors for the detection of foodborne pathogens. And reviews the current advances in microfluidic impedance sensors based on transducer materials and detection techniques, including detection technology based on interdigitated microarrays electrode, electrophoresis technology, nanotechnology, etc. Finally, the challenges and development trends of current microfluidic impedance sensors are discussed.